Sediment pollution by radionuclides and toxic metals in the Ierissos Gulf, North Aegean Sea, Greece - Pappa, F. K.; Tsabaris, C.; Kaberi, H.; Zeri, C.; Androulakaki, E.; Pashalidis, E.; Ioannidou, A.; Kokkoris, M.; Eleftheriou, G.; Patiris, D. L.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
Environmental pollution of industrial areas and especially of areas which contain industries that involve processing of NORM (Naturally Occurring Radioactive Materials), requires monitoring radionuclide activ- ities and trace metal concentration. In the gold mine facility of Stratoni region in Ierissos Gulf, surface sediment samples were analysed regarding TENORM (Technologically Enhanced NORM) and toxic metals (e.g. As, Pb, Cu, Cr and Ni). Radionuclide activity concentrations (226Ra, 214Pb, 214Bi, 210Pb, 228Ac, 212Pb, 212Bi, 208Tl, 40K) were measured by means of gamma-ray spectrometry using a high-purity ger- manium (HPGe) detector, while the trace metals concentrations were determined using the XRF (X-Ray Fluorescence) technique. The results indicate that the surface sediments of the Ierissos Gulf are significantly polluted with As, Pb and Cu. Surface distribution analysis of the studied radionuclides and toxic metals (e.g. TENORM, As, Pb, and Cu) indicates maximum contamination levels close to the factory area, which decrease gradually with increasing distance from the shore. The interpretation of the increased levels is under investigation since the load-out facility of the mining operations in the town of Stratoni affects the whole ecosystem.